2019
DOI: 10.1101/672626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The repertoire of serous ovarian cancer non-genetic heterogeneity revealed by single-cell sequencing of normal fallopian tube epithelial cells

Abstract: The inter-differentiation between cell states promotes cancer cell survival under stress and fosters non-genetic heterogeneity (NGH). NGH is, therefore, a surrogate of tumor resilience but its quantification is confounded by genetic heterogeneity. Here we show that NGH can be accurately measured when informed by the molecular signatures of the normal cells of origin.We surveyed the transcriptomes of ~ 4000 normal fallopian tube epithelial (FTE) cells, the cells of origin of serous ovarian cancer (SOC), and ide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
75
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(87 citation statements)
references
References 115 publications
(116 reference statements)
12
75
0
Order By: Relevance
“…1E and Supplementary Fig. 1G) and functional studies suggest a putative connection to the secretory cell signatures 'Cell Cycle' and 'EMT' [14]. Moreover, IGF2BP1 was recently shown to modulate the cell cycle in an E2F1-dependent manner [32].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…1E and Supplementary Fig. 1G) and functional studies suggest a putative connection to the secretory cell signatures 'Cell Cycle' and 'EMT' [14]. Moreover, IGF2BP1 was recently shown to modulate the cell cycle in an E2F1-dependent manner [32].…”
Section: Discussionmentioning
confidence: 88%
“…EMT, characterized by the loss of CDH1 (E-cadherin) positive cell-cell contacts termed adherens junctions (AJs), is thought to underly progression of the mesenchymal-like subtype. Recent single-cell sequencing and bulk sequencing deconvolution analyses identified cellular HGSOC subtypes on the basis of non-genetic heterogeneity, demonstrating that HGSOC tumours with a high proportion of cells with EMT signature are associated with a worse prognosis [14]. The SRC protein kinase is a crucial activator of AJ disassembly, that initiates EMT, with elevated activity in EOC patients [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In an investigation of functional utility of ovarian cancer cell lines in pre-clinical trial, Coscia et al [50] reported KURAMOCHI as one of the closest resemblance to the tumor samples. A recent study, using deep single cell RNA-Seq data, established this cell line as potential model of ovarian cancer subtype in vitro [51]. Domcke et al [52] reported KURAMOCHI as one of the top cell lines for ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Since the known drug screening data between TCGA samples and cell lines were limited, we included structurally similar drugs in our evaluation. We retrieved PaDEL descriptor [49] of drug's chemical properties and 2D and 3D structural profiles of 378 drugs in GDSC using a line notation of simplified molecular-input line entry system (SMILES) [50] from PubChem [51] database. We computed structural similarities using Pearson correlation between different drugs from TCGA and GDSC.…”
Section: Running Tc Analysismentioning
confidence: 99%
“…In an investigation of functional utility of ovarian cancer cell lines in pre-clinical trial, Coscia et al [52] reported KURAMOCHI as one of the closest resemblance to the tumor samples. A recent study, using deep single cell RNA-Seq data, established this cell line as potential model of ovarian cancer subtype in vitro [53]. Domcke et al [54] reported KURAMOCHI as one of the top cell lines for ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%